Effect of CeO2 morphology on performance of NiO/CeO2 catalyst in combined steam and CO2 reforming of CH4. (23rd May 2019) - Loc, Luu Cam; Phuong, Phan Hong; Putthea, Dang; Tri, Nguyen; Van, Nguyen Thi Thuy; Cuong, Hoang Tien
Nanorods (NR), nanoparticles (NP), and nanocubes (NC) of ceria were prepared by hydrothermal method and used as supports for NiO catalysts for bireforming of CH4 in this investigation. Effects of NiO contents (5-20 wt.%), quantities of reagents, and calcination duration (1-3 h) at 800°C were investigated. Several techniques, including N2 physisorption measurements, X-ray powder diffraction, hydrogen temperature-programmed reduction, scanning electron microscope (SEM), and transmission electron microscopy (TEM) were used to investigate the physico-chemical properties of catalysts. The catalytic performance of the Ni/CeO2 catalysts in combined steam and CO2 reforming of CH4 (bi-reforming) was assessed in the temperature range of 550-800°C. The results revealed that a better duration for calcination is 2 h. After reduction at 800°C for 2 h, catalyst 10 wt% NiO/CeO2 -NR was more active and exhibited much higher activity at lower reaction temperature range than others. The high surface area and better reducibility were responsible for improving performance of this catalyst. Moreover, strong metal support interaction (SMSI) was attributed to the better anti-sintering ability leading to a higher stability with time on stream (TOS) of this catalyst. Besides, this improvement of anti-carbon deposition for 10 wt% NiO/CeO2 -NR catalyst also owned to CeO2 nature of oxygen capacity. At reaction temperature of 700°C, its catalytic performance could remain over 30 h until deactivation initiated. Coke amount formed after 30 h of TOS was found to be as low as 1.84 mgC /gcat by using temperature programmed oxidation technique.